1994
DOI: 10.1192/bjp.165.2.276b
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoceptor activity and adenylate cyclase inhibition in depression

Abstract: CORRESPONDENCE dopamine. In our two healthy volunteers the oppo site may have happened, and the combination of amphetamine with haloperidol may have caused marked dystonia by potentiation of dopamine release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Previous studies demonstrated lower or similar forskolin-stimulated cAMP levels in clinically depressed individuals compared with controls (Abu-Saleh et al., 1994; Gracia-Sevilla et al., 1990; Mazzola-Pomietto et al., 1994; Menninger & Tabakoff, 1997; Newman et al, 1992) or in the brains of suicide victims (Cowburn et al, 1994). This may be the result of modifications in the central and peripheral nervous system generated by the depression itself or by antidepressant drugs (Buckholtz et al, 1988; Ebstein et al, 1988; Ossofsky, 1976) or by changes in brain functions coexhibited with psychiatric morbidity (Davidson et al, 2002).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies demonstrated lower or similar forskolin-stimulated cAMP levels in clinically depressed individuals compared with controls (Abu-Saleh et al., 1994; Gracia-Sevilla et al., 1990; Mazzola-Pomietto et al., 1994; Menninger & Tabakoff, 1997; Newman et al, 1992) or in the brains of suicide victims (Cowburn et al, 1994). This may be the result of modifications in the central and peripheral nervous system generated by the depression itself or by antidepressant drugs (Buckholtz et al, 1988; Ebstein et al, 1988; Ossofsky, 1976) or by changes in brain functions coexhibited with psychiatric morbidity (Davidson et al, 2002).…”
Section: Discussionmentioning
confidence: 89%
“…In clinically depressed patients, forskolin-stimulated cAMP levels were found to be lower than controls (Cowburn et al., 1994; Menninger & Tabakoff, 1997) or similar to them (Newman et al, 1992). Also, contrasting results were reported for cAMP stimulation with prostaglandin E1 or via Beta-adrenergic receptors (Abu-Saleh et al, 1994; Garcia-Sevilla et al, 1990; Mazzola-Pomietto et al, 1994).…”
Section: Introductionmentioning
confidence: 85%
“…6 However, the most commonly used methodology for studying adenylyl cyclase activity is through direct measurement of cAMP accumulation from adenosine 5'-triphosphate (ATP) following agonist stimulation. 32 P-radiolabeled ATP is converted to 3 2 P cAMP, which is then separated and quantified through a double-step Dowex-neutral alumina chromatography. 7 The traditional methodology from Salomon 7 can be summarized as follows.…”
Section: Methodowgic Tools For Study-ing Adenylyl Cyclase Activitymentioning
confidence: 99%
“…The final eluate, obtained with imidazole, is collected in scintillation vials. The sample radioactivity is then analyzed by liquid scintillation/duallabel [ 32…”
Section: Methodowgic Tools For Study-ing Adenylyl Cyclase Activitymentioning
confidence: 99%
See 1 more Smart Citation